Performance management: Quo Vadis? - LIEVENS, Filip (Institutional Knowledge at Singapore Management University, 2020)
Traditionally performance management has been described as a powerful tool in Human Resource Management (HRM) because it has potentially a wide array of application possibilities for various HR topics. However, the reality in practice is different. Various surveys reported that more than 90 percent of the performance management systems are unsuccessful. Further studies have shown that up to 75% of staff feel that their organization’s performance management system does not help them to improve their performance and is largely a waste of time (e.g., Capelli & Tavis, 2016; Pulakos, 2009). Economic analyses of the return on investment (as compared to the costs and time spent) on performance management activities appear to confirm these negative perceptions (e.g., CEB, 2012). What are the reasons for failure in the area of performance management? In this article, we aim to identify the main problems with the current performance management systems. At the same time, we aim to present a wide array of possible solutions to these recurring issues. All of this should further stimulate the debate about how to revamp performance management systems in organizations.